Intention to Seek Counseling Among Indonesian Students: Examining the Impact of Social Anxiety and Loneliness - Maba, Aprezo Pardodi; Saputra, Andika Ari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2019)
This study was investigating the impact of social anxiety and loneliness toward intention to seek counseling, and loneliness as mediator in the relation of social anxiety towards intention to seek counseling. The participants were selected with cluster random sampling technique. Five hundred and two students from several regions in Indonesia were involved after confirm the participant consent and complete the online instruments of brief scale of loneliness for adolescents (Î± = 0.709), social anxiety (Î± = 0.780), and intention to seek counseling (Î± = 0.746). The analysis data technique was used path analysis with mediation variable. The results of this study showed that, separately social anxiety and loneliness affected the intention to seek counseling, social anxiety affected loneliness, social anxiety with loneliness affected the intention to seek counseling, and the direct effect of social anxiety toward intention to seek counseling is higher than through loneliness as mediator variable.